From the lagoon-city to the lagoon of adaptive cities - Filippo Magni; Giulia Lucertini; Katia Federico (TeMA: Journal of Land Use, Mobility and Environment, 2024)
The impacts of climate change and the increasing occurrence of consequent extreme events in recent years have led to significant environmental, social and economic consequences in a fragile and highly vulnerable territory such as Venice. It is precisely in this perspective, which considers areas particularly vulnerable to the effects of climate, that the scientific research program Venezia2021, coordinated by CORILA - Consortium for coordination of research activities concerning the Venice lagoon system, is inserted. The research in question involves a complex process of identification and integration of innovative tools, data processing and analysis and assessment of impacts, in order to contribute to the maintenance of a proper balance of the lagoon ecosystem in a perspective of increased climate resilience.